A Rare Case of Congenital Diabetes Insipidus - Rege, Tanvi; Polsani, Srujana; Jim, Belinda (Frontiers in Medicine, 2015)
Congenital nephrogenic diabetes insipidus (NDI) is a conformation disease resulting from protein misfolding. Ninety percent of mutations result from the inactivating mutations of the arginine vasopressin receptor 2 (AVPR2) gene transmitted in an X-linked fashion, blocking the response to vasopressin, resulting in the inability to concentrate urine. Clinical features include polyuria, polydipsia, dehydration, and hypernatremia. They are generally more severely in affected males but present variably in females due to skewed inactivation of the X chromosome. We describe a case of a 40 year old woman with a history of Type 2 diabetes mellitus, hyperlipidemia, and obesity who presents with debilitating polyuria since the age of five with no clear diagnosis. Interestingly, her son was subsequently diagnosed with NDI. Genetic testing revealed that she was heterozygous for the Val88Met mutation in the AVPR2 gene while her son was hemizygous for the same. The patient has since been successfully treated with diuretics and a low solute diet. We highlight that although X-linked NDI patients are mostly males, it should be considered in symptomatic females to prevent delays in the diagnosis. Conformational diseases such as NDI are presently the subject of research using pharmacological chaperones to restore proper receptor membrane localization and function.